Meningkatkan Pemahaman Makna Konteks Tuturan melalui Bahasa â€œPlesetanâ€ pada Lagu-lagu Populer Indonesia - Kusumaningsih, Dewi; Nuurâ€™ainii, Zahra Lintang; Marmoah, Sri; Nurhasanah, Farida (Universitas Batanghari Jambi, 2023)
The emergence of new languages led to the occurrence of interesting language phenomena, one of which was the language of plesetan. People's language skills are increasingly creative in expressing critical things, including those that are political. This study aims to describe the forms and types of plesetan language games. This research uses a descriptive qualitative approach.Â The object of this study is specifically determined in the lyrics of popular songs in Indonesia taken from online media. Data in the form of words or sentences in the lyrics of popular songs in Indonesia. Data is transcribed from images and converted into sentences and/or words. Data was collected using documentation, reading, and transcript techniques. The data triangulation technique used, namely source triangulation, is to check several related sources to test the credibility of research data.Â The data analysis process is carried out using a qualitative model from Miles and Huberman through 3 steps, namely data reduction, data display, and drawing conclusions. The results showed that the plesetan language games that appeared in the lyrics of popular songs in Indonesia proved that people's language skills are increasingly creative in expressing critical things, including political ones. Discussing the use of plesetan language, will be able to increase people's insight in responding to and using pun language, especially in understanding the context of speech in the missed song